A collage of us: Ágota Kristóf and the imaginary (Balthazar, 2023)
Can Ágota Kristóf's narratives, whether in prose, verse, or for the theatrical stage, create shareable imagery? In this contribution we investigate the extent to which Ágota Kristóf's gambling with the strings of her characters can affect us all.
Keywords: empathy; identity; imaginary; literature; Ágota Kristóf; Susan Sontag